(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the ingestive behavior of Nellore steers fed with diets containing encapsulated urea or not, in four periods of the termination of the confined animals. 32 and 28 were used; 24 and 21; 16 and 14; 8 and 7 animals for diets without and with urea encapsulated in the 1st; 2nd; 3rd and 4th periods, respectively. Each period consisted of 50 days, with the exception of the last period that had 45 days. The animals were confined in individual pens. Each evaluation, within the period, was 48 consecutive hours, with 10-minute observation intervals. The experimental design was completely randomized in a 2 x 4 factorial arrangement and for the comparison of means, the student’s “t” test was used. There was interaction between diets and evaluations in the periods for dry matter consumption and rumination efficiency, and for the other variables studied there was no interaction. The leisure time was longer and the rumination time was shorter for the animals that received the diet without encapsulated urea in relation to the diet with encapsulated urea. The feeding time of the animals was longer for the evaluation of the second period, but it did not differ from the first and fourth periods. Leisure time was longer in the second period and similar to the third period. Ingestive behavior is altered at different periods of confinement and by the composition of the diet.